Institutional investors and stock market volatility. Evidence from Korea. Issue 6 (29th March 2020) - ikizlerli, Deniz
ABSTRACT: This article examines the impact of institutional investors on return volatility in Korea stock market from 4 January 2000 to 15 September 2017 using actual trading data. We find that net purchases of institutions increase the market level of volatility but find no evidence that trades by institutional investors had a destabilizing impact on Korea's equity market over our sample period.